The Influence of Green Investment on Investment Intention Among Generation Z in Indonesia: The Moderating Role of Financial Literacy - Utami, Novia (Transpublika Publisher, 2025)
As environmental concerns continue to rise, sustainable investment has gained increasing attention, particularly among young investors. However, despite the growing awareness of environmental issues, the level of investment intention in green assets among Generation Z remains relatively low. This study investigates the impact of green investment on investment intention among Generation Z in Indonesia, with financial literacy as a moderating variable. Using a quantitative approach, data were collected from 538 Generation Z respondents. The analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The findings reveal that green investment has a significant positive effect on investment intention. Moreover, financial literacy strengthens this relationship, highlighting its moderating role. These results emphasize the importance of enhancing financial literacy to encourage sustainable investment decisions among Generation Z. This study contributes to the literature on green finance by providing empirical evidence on the role of financial literacy in shaping young investors’ sustainable financial behavior.